From Bilateral Arbitral Tribunals and Investment Courts to a Multilateral Investment Court Options Regarding the Institutionalization of Investor-State Dispute Settlement - Bungenberg, Marc (Special Issue,, 2018)
This book considers the potential setup for a future Multilateral Investment Court (MIC). The option of an MIC was first discussed by the EU Commission in 2016 and has since been made an official element of the EU Common Commercial Policy. In 2017, UNCITRAL also decided to discuss the possibility of an MIC, and on 20 March 2018, the Council of the EU gave the EU Commission the mandate to negotiate the creation of an MIC. The "feasibility study" presented here is intended to contribute to a broader discussion on the options for a new international court specialized in investment protection. The cornerstones of such a new permanent court are a strict orientation on the rule of law, reduced costs of investment protection, transparency considerations, aspects of consistency in case law, and the effective enforceability of MIC decisions.